The ethics challenge in public service a problem-solving guide - Lewis, Carol W. (Carol Weiss), 1946- (Jossey-Bass, 2012)
"This thoroughly revised and updated third edition of The Ethics Challenge in Public Service is the classic ethics text used in public management programs nationwide. It also serves as a valuable tool for public managers who work in a world that presents more ethical challenges every day. It contains a wealth of practical tools and strategies that public managers can use when making ethical choices in the ambiguous pressured world of public service. The book contains new material on topics including social networking, the use of apology, ethics as applied to public policy, working with elected officials, and more"--